(untitled) (Global Journal of Human-Social Science, 2023)
With the development of science and technology and media information great changes have taken place in communication methods Images music gestures or written language all play important roles in daily communication besides of spoken language This study selects Apple Event 2018 as the research subject based on Halliday s Systemic Functional Linguistics Framework and Zhang Delu s modal synergy theory to analyze the selection combination relationship and multimodal application of modes in product launch conference in order to realize the interpersonal functional meaning of Halliday s Metafunction Theory under the coordination of multiple modes